1985
DOI: 10.2337/diacare.8.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Normoglycemia Before Conception on Early Pregnancy Hormone Profiles

Abstract: Insulin-dependent diabetic women have been shown to have subnormal hormone levels in the first trimester of pregnancy. To determine whether these abnormalities were the result of poor diabetes control, testosterone, androstenedione, human chorionic gonadotropin (HCG), and prolactin were studied longitudinally in diabetic women made normoglycemic before conception (N = 11) and normal (N = 6) control subjects beginning at the fifth week of gestation. HCG levels rose normally in all 11 diabetic and six control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Therefore, the decreased level of these hormones in diabetic women during gestation may have restrained the development of an overtly hyperlipidemic condition in our diabetic pregnant patients. Other authors also have reported decreased plasma estradiol and prolactin levels in pregnant diabetic women who had wide glycemic excursions (43,44) that mainly corresponded to the first trimester of gestation. In a recent study, decreased plasma cholesterol and TG levels have even been found in early pregnant diabetic women with enhanced HbA 1c values (45), and although hormonal levels have not been analyzed, they also would be expected to be decreased.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the decreased level of these hormones in diabetic women during gestation may have restrained the development of an overtly hyperlipidemic condition in our diabetic pregnant patients. Other authors also have reported decreased plasma estradiol and prolactin levels in pregnant diabetic women who had wide glycemic excursions (43,44) that mainly corresponded to the first trimester of gestation. In a recent study, decreased plasma cholesterol and TG levels have even been found in early pregnant diabetic women with enhanced HbA 1c values (45), and although hormonal levels have not been analyzed, they also would be expected to be decreased.…”
Section: Discussionmentioning
confidence: 90%
“…We therefore propose that the decreased estradiol levels in our diabetic patients impede an exaggerated rise of circulating lipoproteins above the normal range. Because the degree of metabolic control may affect both the dyslipidemic condition of the diabetic patient (12,15,46) and the level of sex hormones during pregnancy (43,44), we propose that the development or lack of development of exaggerated hyperlipidemia in diabetic pregnancy depends on the balance between these two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Jovanovic et al [16] reported that early PRL levels were lower than established population reference ranges in a cohort of patients with suboptimally controlled T1DM, with levels only entering the normal range after glycaemic control was achieved after 14 weeks. A later study by the same group [17] found no difference between first-trimester PRL in patients with T1DM compared with controls, a finding that was attributed to the earlier (pre-conception) achievement of glycaemic control in that particular cohort.…”
Section: Prolactin In Pregnancies Affected By Pregestational Diabetesmentioning
confidence: 84%
“…Normalisation of PRL secretion has been hypothesised to be related to glycemic control before conception. 105 Some studies comparing serial PRL levels in T1DM pregnant women to healthy controls, have reported lower PRL levels in diabetic women. [106][107][108] Others have noted that human chorionic gonadotropin (hCG) and 17 beta estradiol (E2) levels are often reduced in patients with TDM1 during early pregnancy, particularly in the case of poor glycemic control.…”
Section: Prolactin In Women Affected By Pregestational Diabetes Mellitusmentioning
confidence: 99%
“…No difference in PRL values was found within the first trimester in both groups. Normalisation of PRL secretion has been hypothesised to be related to glycemic control before conception 105 …”
Section: Prolactin Effects On Pancreatic β‐Cellsmentioning
confidence: 99%